Effect of organic and inorganic nutrient application in vegetable pea on growth, yield and net return from succeeding maize in vegetable peaâ€“maize cropping sequence - Wanniang, Samborlang K.; Singh, A.K.; Ram, V.; Das, Anup; Ray, Lala I.P.; Singh, N. Janaki (Indian Journal of Hill Farming, 2019)
A two years field experiment was conducted during Rabi and Kharif seasons of 2014-15 and 2015-16 to study the effect of integrated nutrient management practices in vegetable pea-maize cropping sequence on experimental farm of the College of Post graduate Studies (CAU-I), Umaim (Meghalaya). In this investigation, residual effect of organic and inorganic nutrient sources applied in vegetable pea, was assessed on growth, yield and net return from succeeding maize. The experiment was laid out in factorial randomized block design on maize variety â€œDA 61Aâ€. This study included three reatments viz. farmyard manure (FYM) (5 t ha-1) (B1), Rhizobium + Phosphorus solubilizing bacteria (PSB) (B2) and FYM (5 t ha-1) + Rhizobium + PSB (B3) under organic sources and six treatments viz. recommended dose of fertilizer (RDF) (F1), RDF + Lime (0.5 t ha-1) (F2), 75 % RDF (F3), 75 % RDF + Lime (0.5 t ha-1) (F4), 50% RDF (F5) and 50 % RDF + Lime (0.5 t ha-1) (F6) under inorganic nutrient source to preceding vegetable pea. Maize was grown as a succeeding crop after pea harvest with 50% of recommended dose of N, P and K fertilizers (RDF) to maize. The result shown that both the nutrient sources applied to preceding vegetable pea crop had significant effect on growth, yield attributes and yields of succeeding maize in both the years. B3 application in pea was at par with B1 (FYM 5 t ha-1) application to pea but significantly more over B2 application to pea in both the years. Among inorganic nutrient application to preceding pea, F2 recorded maximum grain yields in succeeding maize which was at par with F1, F3 and F4 applications to pea in first year but significantly more over the maize grain yield recorded from F5 and F6 application to pea. In second year again F2 recorded maximum grain yields in succeeding maize which was at par with F1 and F4 applications to pea but significantly more over the F3, F5 and F6 application to pea. Net return (â€˜000â‚¹ ` ha-1) recorded from maize from B3 organic treated plots was 13.37 and 14.12 and through F2 inorganic treated plots was 17.4 and 16.0 on succeeding maize in first and second year, respectively. Interaction between organic and inorganic nutrient sources applied to vegetable pea was also found significant for in second year when maximum grain yield (3.82 t ha-1) and net return (â‚¹ 22.46â€™ 000 ha-1) of succeeding maize was obtained with the combine application of biofertilizers + FYM 5 t ha-1 + RDF + Lime 0.5 t ha-1 (B3F2).